Paraletteratura: i limiti di un concetto critico nella definizione dei generi letterari (Comparatismi, 2025)
In Italy, genre fiction has long been dismissed as a marginal literary form, and the full range of its manifestations has been labelled paraliterature, a term that often generates misunderstanding and confusion. This paper argues that such a view (and division) is not only extremely limited, and limiting, when it comes to addressing the complexity of literary phenomena, but also that, by focusing solely on the literary dimension of genre, it fails to account for the complex features that genre has acquired in the present. The first part of this paper examines a number of critical works that, in France and Italy, make a distinction between “proper” literature and paraliterature (Ricci, Rak, Spinazzola, Couégnas, Simonetti). By using science fiction as a case study and adopting the frameworks proposed by John Rieder and Damien Broderick, the second part explores alternative definitions of the concept of genre that include an understanding of its complexity, its transmedia dimension, and the publishing and material dynamics underlying its production.
Keywords: Paraliterature; Genre fiction; Literary genre; Science fiction; Contemporary fiction